Muscarinic acetylcholine receptor activation prevents disinhibition-mediated LTP in the hippocampus - Takkala, Petri; Woodin, Melanie A. (Frontiers in Cellular Neuroscience, 2013)
Disinhibition-mediated long-term potentiation (LTP) in the CA1 region of the hippocampus involves GABAergic synaptic plasticity at feedforward inhibitory inputs, resulting in the reduced shunting of glutamatergic excitatory currents. The GABAergic plasticity which underlies disinhibition-mediated LTP results from a Ca2+-dependent decrease in the activity of the K+-Cl- cotransporter (KCC2), depolarizing the reversal potential for GABAA receptor-mediated currents (EGABA), thereby attenuating inhibition. Muscarinic acetylcholine receptor (mAChR) activation has previously been shown to regulate classic glutamatergic LTP, modulate intracellular [Ca2+] and signaling, and facilitate the excitability of GABAergic interneurons in the CA1. Based on these effects, and the ability of mAChR activation to regulate CA1 pyramidal neuron KCC2 expression, we proposed that mAChR activation would modulate disinhibition-mediated LTP. To test this prediction, we made whole cell recordings from CA1 pyramidal neurons in hippocampal slices. Disinhibition-mediated LTP was induced using a spike timing-dependent plasticity (STDP) protocol, which involved coincident presynaptic stimulation and postsynaptic current injection (at 5 Hz for 60 seconds). We found that mAChR activation via carbachol (CCh) prevented the induction of disinhibition-mediated LTP. Moreover, in the presence of CCh, EGABA failed to depolarize following plasticity induction. Lastly, we recorded the paired-pulse ratio (PPR) during the induction of disinhibition-mediated LTP and found that in the presence of CCh, plasticity induction induced a significant paired-pulse depression. This suggests that presynaptic mAChR activation may prevent the postsynaptic expression of disinhibition-mediated LTP.